Updating viral agents in tomato seeds with new generation diagnostic technologies - Atik, Ayşen Kübra; Paylan, İsmail Can (Frontiers in Sustainable Food Systems, 2023)
The aim of this study is to identify and update the list of viral pathogens in tomato seeds, which plays an important role for our country's economy, and to control, on behalf of our country, viral factors like TYLCV and PepMV, which were thought not to be existing in the past but were determined by new and sensitive methods in the recent years. It is also the aim, if viral pathogens like TYLCV and PepMV are found, to share this findings with the necessary institutions and to update the viral factors which needs to be tested, and the quarantine lists. Two hundred and thirty-eight seed samples were used in this study. Serological and molecular methods were used in order to identify the viral pathogens in the seed samples. Two hundred and thirty-eight seed samples of different tomato varieties were tested in order to prove the possible existence of Tobacco mosaic tobamovirus (TMV), Tomato mosaic tobamovirus (ToMV), Cucumber mosaic cucumovirus (CMV), Tomato yellow leaf curl geminivirus (TYLCV), Tomato spotted wilt tospovirus (TSWV), Pepino mosaic potexvirus (PepMV), Pepper mild mottle tobamovirus (PMMoV), and Tomato brown rugose fruit tobamovirus (ToBRFV) and as a result 12% of the seeds were founded to be infected with TMV, 23% with ToMV and 8% with CMV. Within the scope of this study it was seen that some seed samples have mixed infections. Sixty-seven seeds of the 238 seeds has been found to be infected in this study. This is a rate of 28% were the seeds are infected at least with one viral pathogen.